2005
DOI: 10.1007/s10897-005-0412-3
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Family Communication About Predictive Genetic Testing: Probands’ Perceptions

Abstract: The responsibility of informing relatives that predictive genetic testing is available often falls to the proband. Support is required during this process, however the perceived utility of genetic counseling and other strategies to facilitate communication have not been explored. We investigated the experiences of 12 individuals with hereditary nonpolyposis colorectal cancer (HNPCC) in a semistructured telephone interview. Respondents informed their immediate family about the availability of genetic testing, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
113
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 20 publications
7
113
0
2
Order By: Relevance
“…Several survey-based studies have found that anxieties about genetic testing vary more in cases where the test is diagnostic but the disease is untreatable and additionally have higher anxiety in cases of cancer when the test is not diagnostic than in cases where treatment is known and effective (Shaw and Bassi 2001;Gaff et al 2005). Lastly, in order for a FH screening program to be effective, individuals need to be willing to make behavioral changes to treat FH.…”
Section: Discussionmentioning
confidence: 99%
“…Several survey-based studies have found that anxieties about genetic testing vary more in cases where the test is diagnostic but the disease is untreatable and additionally have higher anxiety in cases of cancer when the test is not diagnostic than in cases where treatment is known and effective (Shaw and Bassi 2001;Gaff et al 2005). Lastly, in order for a FH screening program to be effective, individuals need to be willing to make behavioral changes to treat FH.…”
Section: Discussionmentioning
confidence: 99%
“…2 Individual characteristics and patterns of family behaviour and relationships, disease characteristics and cultural factors may withhold or delay disclosure of genetic information to atrisk relatives, even when consultands see this as their personal responsibility. [3][4][5][6][7] Although guidelines recommend that professionals should not contact family members directly, that also state that professionals should actively encourage consultands to transmit relevant risk information to relatives and support them throughout the communication process; however, there is lack of clarity regarding how this should be done. 8,9 There has been some discussion on how to cascade information about genetic health risks to the relatives of patients with familial hyper-cholesterolaemia, including the active contacting of relatives directly by professionals, although this depends entirely upon information provided by the proband.…”
Section: Introductionmentioning
confidence: 99%
“…The development of these guidelines took several years, multiple consultations with clinicians and community and brought to the fore many concerns that people have about this issue, although it is stated clearly up front that situations in which such disclosure by the health professional may be required are rare. 18 Although communication of information about genetic conditions within families is seen as a central component of genetic consultations, 19 the interim audit of over 500 routine consultations at general genetics clinics, not the specialized cancer or cardiac clinics, found that only 5% were being seen for reasons that warranted disclosure of genetic information to family members. Therefore, in the professional experience of a genetic health professional, the magnitude of the need for clients attending general genetics clinics to be counselled about disclosure of genetic information is small.…”
Section: Discussionmentioning
confidence: 99%
“…7 It seems likely that most relatives would intend to pass on genetic risk information and that, where this does not occur (non-disclosure), this is usually a 'passive' failure to disclose rather than the proband actively avoiding communication. 8 We suggest that there is a role for health professionals in supporting probands in relation to 'passive' non-disclosure. There has been much debate about how health professionals should be involved with this process; the extent to which this is deemed important appears to vary according to the information that can be made available and the condition that is involved.…”
Section: Introductionmentioning
confidence: 94%